KAJIAN KETEBALAN TANAH LIAT SEBAGAI BAHAN DIELEKTRIK KAPASITOR PLAT SEJAJAR - Jumingin, Jumingin; Setiawati, Susi (Faculty of Mathematics and Natural Science, Universitas PGRI Palembang, 2016)
Research on the study of the clay thickness as a parallel plate capacitor dielectric material has been carried out in the Laboratory of Physics, Faculty of Mathematics and Natural Sciences University of PGRI Palembang from May to July 2013. This study aimed to analyze the effect of dielectric material and the the clay thickness to the capacitance of parallel plate capacitor. This research used experimental methods, where clay samples were made of 3 x 5 cm size with a thickness variation of 2, 4, 6, 8, 10, 12, 14, 16, 18, and 20 mm. The results obtained showed that the use of clay as a dielectric material increased the capacitance of a parallel plate capacitor. The capacitance values in the thickness of 2, 4, 6, 8, 10, 12, 14,16, 18, and 20 mm were respectively 4.2; 3.2; 3.0; 2.5; 2.2; 2.0; 1.9; 1.8; 1.6; and 1.4 pF for air dielectric material and 128, 118, 115, 105, 98, 92, 89, 74, 67, and 65 pF for clay dielectric material. There was a tendency of the greater thickness of the dielectric material, the smaller the capacitance of a capacitor. Keywords: dielectric material, capacitance, clay ABSTRAK Penelitian tentang kajian ketebalan tanah liat sebagai bahan dielektrik kapasitor plat sejajar telah dilakukan di Laboratorium Fisika Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas PGRI Palembang pada bulan Mei sampai Juli 2013. Penelitian ini bertujuan untuk menganalisis pengaruh penggunaan bahan dielektrik tanah liat dan ketebalan bahan dielektrik terhadap kapasitansi yang dihasilkan pada kapasitor plat sejajar. Penelitian ini menggunakan metode eksperimental, dimana sampel tanah liat dibuat dengan ukuran 3x5 cm dengan variasi ketebalan 2, 4, 6, 8, 10, 12, 14, 16, 18, dan 20 mm. Hasil yang diperoleh menunjukkan bahwa penggunaan tanah liat sebagai bahan dielektrik meningkatkan nilai kapasitansi suatu kapasitor plat sejajar. Nilai kapasitansi pada ketebalan 2, 4, 6, 8, 10, 12, 14,16, 18, dan 20 mm adalah 4,2; 3,2; 3,0; 2,5; 2,2; 2,0; 1,9; 1,8; 1,6; dan 1,4 pF untuk bahan dielektrik udara dan 128, 118, 115, 105, 98, 92, 89, 74, 67, dan 65 pF untuk bahan dielektrik tanah liat. Ada kecenderungan semakin besar ketebalan bahan dielektrik, semakin kecil nilai kapasitansi suatu kapasitor. Kata kunci : Bahan dieletrik, kapasitansi, tanah liat